ANALISIS HUKUM PENGGUNAAN FREKUENSI RADIO TANPA IZIN BERDASARKAN UU NO.36 TAHUN 1999 TENTANG TELEKOMUNIKASI (Studi putusan Pengadilan Negeri Salatiga Nomor 91/Pid.B/2013/PN.Sal) - Hanawi Aananda Putra Sitohang; Muhammad Hamdan; Mahmud Mulyadi; Jelly Leviza (USU LAW JOURNAL, 2016)
ABSTRACT The use of radio frequencies must obtain permission from the government, before obtaining permission still broadcasting, radio broadcasting institutions must go through the trial broadcast period of 6 (six) months. Broadcasting licenses that have been granted are prohibited transferred (given, sold, or otherwise transferred) to another party (other legal entities or other persons). While the act of taking without permission outside the consent or will of the owner (against the law) called the theft of the book of criminal law. The element Regulation frequency use without the permission of "whoever", "Who" denote the subject of law and the word "something good" in question is a radio frequency that the user must obtain permission from the government, but accountability for perpetrators who violate them can be sentenced to imprisonment and fines. Efforts to enforce laws against the crime of use of radio frequencies may be used without permission stretcher adminnistratif sanction of revocation of consent after being given a written warning, and counseling to the relevant parties this provision is intended as the government's efforts in monitoring and controlling the operation of Telecommunications. Keywords: Frequency Without Permission.